Teachers’ digital literacy - Ribeiro, Maria Isabel (2021)
Currently, digital skills are considered a decisive requirement for personal fulfillment and development, active citizenship, social inclusion and employment in the knowledge society. In this context, this research aimed to consolidate the existing research in the field of digital literacy among teachers. In methodological terms, this research was based, in a first stage, on the PRISMA statement and, in a second stage, on bibliometric analysis. For this, a search was developed, in March 2021, in the Scopus database being selected 96 publications based on the combination of the terms "ICT", "skills", "digital", "literacy", "education" and "teachers". Subsequently, a chronological filter was used limiting the research period from 2010 to 2020 being counted 80 publications. Then, this research was limited to “Article” and “Review” documents subject to double blind referee (46) published in English, Spanish, Portuguese and French (44). Finally, abstracts and, when necessary, the entire text was selected, in order to verify the relevance of publications for this research, considering the following criteria: study location, type of study, objectives, sample size and contributions, totaling 27 articles. The elaboration of the bibliometric analysis was done using the VOSviewer software, version 1.6.16 and the binary counting method. The minimum number of occurrences was set at five. Three thematic approaches that were related to each other were identified. The first included the terms "Area", "Communication", "Communication technology", "Digital competences", "Information", "Level" and "Training". This approach covered all publications that used instruments to measure the level of digital skills of teachers and identified factors that are determinants of these skills, namely, the area of training, the level of education in which teachers work, teaching experience, age, gender, among others. The second approach included the terms "Attitude", "Experience", "ICT integration", "ICT skills", "Implementation", "New Technology" and "Teacher training". In general, these publications described the digital literacy practices of teachers, the difficulties of implementation, with special attention, on teachers’ knowledge and attitudes. Finally, the third approach focused essentially on the question "how to equip teachers with the knowledge and skills needed in the digital age?" This approach included all publications with the terms, "Learning", "Process", "School" and "Technology", being associated, especially to the use of technologies in the classroom as an instrument to improve digital learning, which promotes changes in digital thinking and behavior between teachers and students, despite the existing challenges and limitations, such as the inadequate installation of ICT, time restrictions, the actors’ limitation of competencies, the attitudes and motivation of teachers in the use of technologies, among others.